2019
DOI: 10.1080/09540105.2019.1566301
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent immunochromatographic strip using quantum dots for 3-amino-5-methylmorpholino-2-oxazolidinone (AMOZ) detection in edible animal tissues

Abstract: To monitor the levels of furaltadone in animal tissues, an immunochromatographic strip (immunostrip) based on quantum dot was developed for rapid detection of 3-amino-5methylmorpholino-2-oxazolidinone (AMOZ), the metabolite of furaltadone. Four monoclonal antibodies (mAbs) against nitrophenyl derivative of AMOZ (2-NP-AMOZ) were generated from the hybridoma cell lines. Among them, the mAb 5C10/3A8 showed the highest sensitivity to 2-NP-AMOZ. Using an immunostrip reader, with the 2-NP-AMOZ as the target, the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…From the above results, the test strip can be used for detecting the furaltadone metabolite AMOZ in catfish samples and is largely immune to matrix interference. When compared with previous immunoassays (Xie et al, 2019;Zhang et al, 2018) for the detection of AMOZ, this strip assay could detect AMOZ with a lower vLOD and cut-off value, and a greater sensitively. Moreover, the strip assay was more convenient and AMOZ spiked into the samples could be detected directly.…”
Section: Detection Of Amoz In Catfish Samples By Strip Assaymentioning
confidence: 95%
See 1 more Smart Citation
“…From the above results, the test strip can be used for detecting the furaltadone metabolite AMOZ in catfish samples and is largely immune to matrix interference. When compared with previous immunoassays (Xie et al, 2019;Zhang et al, 2018) for the detection of AMOZ, this strip assay could detect AMOZ with a lower vLOD and cut-off value, and a greater sensitively. Moreover, the strip assay was more convenient and AMOZ spiked into the samples could be detected directly.…”
Section: Detection Of Amoz In Catfish Samples By Strip Assaymentioning
confidence: 95%
“…Immunoassays have the advantages of high sensitivity, rapid turnaround times, and high throughput (Gu et al, 2015;Li et al, 2020;Tan et al, 2020) and numerous studies have reported their use in the detection of AMOZ in aquatic animals, chicken, pork, beef, and eggs (Wang et al, 2019;Q. Wang et al, 2018;Xie et al, 2019). Although these immunoassays can detect AMOZ in a variety of sample types, detection limits are high.…”
Section: Introductionmentioning
confidence: 99%
“…There was a good correlation (R 2 =0.9901) between the results given by the immunostrip and LC-MS/MS. Hence, the method could be used for the rapid and quantitative detection of AMOZ residues in edible animal tissues (Xie et al, 2019).…”
Section: Quantum Dot Immunochromatographic Assaymentioning
confidence: 99%
“…The amount of FM-mAb captured on the T and C lines is different; therefore, the lines present colours of different strength. The values of the T and C lines at different Cd concentrations is determined with a strip reader (Xie, Wu, Shi, & Le, 2019). The detection performance of the fluorescent test strip is evaluated by establishing a standard curve.…”
Section: Quantitative Detection Using the Fluorescent Immunoassay Stripmentioning
confidence: 99%